„Gazeta Warszawska” księdza Stefana Łuskiny o podróży Stanisława Augusta Poniatowskiego do Kaniowa w 1787 r. - Karkocha, Małgorzata (Przegląd Nauk Historycznych, 2011)
Presented article is aimed at discussing the five-month journey (from 23 February to 22 July 1787) of the king Stanisław August Poniatowski to Kaniów, where the monarch was supposed to meet with the Russian empress Catherine II. This issue has not interested any of Polish historians so far. The source of information used by us are the reports placed on the pages of „Gazeta Warszawska” – the main magazine being published in the capital city of the Polish-Lithuanian Commonwealth in years 1774–1793. Stanisław August had great hopes about the journey to Kaniów. He expected that he would obtain from Catherine II the guarantee of the sanctity of the territorial state and the assent to some political reforms, including the increase in the number of army, in exchange for the military alliance and the aid in the imminent Russo-Turkish war. He counted also on gaining new territory in the form of the part of Moldavia and Bessarabia. Stanisław August set out on the trip on 23 February 1787. He reached his destination on 24 March. The meeting with Catherine II took place on the empress’ gallery in the middle of Dnepr on 6 May, and it took only a few hours, instead of few days, like it was decided earlier. Despite of this fact Polish ruler was satisfied. He believed that it would bring the Polish-Lithuanian Commonwealth a lot of weal and the longed-for peace. It’s time to show how much the king was mistaken.